FOREIGN EXPERIENCE OF ESTABLISHMENT AND DEVELOPMENT OF ECOLOGICAL TOURISM AND ITS USE OPPORTUNITIES IN UKRAINE - Безугла, Людмила (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2021)
Currently, eco-tourism is recognized as one of the main directions of development of the tourism industry, which has an important role in shaping and ensuring sustainable development. The article considers the characteristic features of European models of organization of ecological (green) tourism: British, French, German, Italian, Czech, Spanish, Polish and Latvian. The peculiarities of ecotourism development in different countries of the world (Italy, Austria, Finland, Spain, Germany, Great Britain, Hungary, Romania, Poland, Cyprus) are studied. The essence of tax mechanisms applied in a number of countries of the world for the purpose of stimulation of development of ecological tourism is studied. It is established that the experience of developed countries should be used in the modern conditions of Ukraine, but taking into account the specifics of the national economy. The development of ecological tourism in Ukraine is possible with the use of marketing communications, involvement of international organizations to promote the latest technologies in this area, ensuring public awareness, which will improve the ecotourism infrastructure in the regions. Priority areas for the development of ecotourism in Ukraine, taking into account foreign experience are: improving the regulatory framework and its implementation to the main provisions of international law; introduction of a tax mechanism based on the provision of appropriate benefits; formation of proper ecotourism infrastructure; providing national nature parks with recreational and tourist infrastructure that will meet international standards; intensification of cooperation between authorities, investors, business structures, higher education institutions, scientific institutions; search for additional and non-traditional sources of funding; public involvement through conducting relevant sociological surveys of public opinion, studying the positions of the local population and visitors, the formation of public associations; development of ecotourism development strategy with the use of marketing tools and information technologies.